2011
DOI: 10.1002/dev.20576
|View full text |Cite
|
Sign up to set email alerts
|

Development of hand preference for object‐directed actions and pointing gestures: A longitudinal study between 15 and 25 months of age

Abstract: The development of hand preferences for object-directed actions and pointing gestures was investigated in toddlers sampled bimonthly between 15 and 25 months of age. Language level was also assessed, in an attempt to examine the relationship between handedness and language development. Results did not reveal any changes over the study period in the mean Handedness Index of the whole sample, both for bimanual manipulative activities and pointing gestures. However, the categorization of participants as left-hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
1
13
0
1
Order By: Relevance
“…In contrast to the 4-and 5-year old children, 3-year-olds showed no hand preference for picking up the LEGO 1 pieces, nor did they show any preference for which hand performed the passive, holding role or the active, manipulative role. This was surprising, as previous research has shown a right hand preference in 2-and 3year-old children for holding and manipulating objects (i.e., getting a toy out of a tube; Cochet, 2011;Cochet et al, 2011;Fagard & Lockman, 2005). It could be argued that pointing to an object or extracting a toy from a tube is ''simpler'' than constructing models with LEGO 1 pieces.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast to the 4-and 5-year old children, 3-year-olds showed no hand preference for picking up the LEGO 1 pieces, nor did they show any preference for which hand performed the passive, holding role or the active, manipulative role. This was surprising, as previous research has shown a right hand preference in 2-and 3year-old children for holding and manipulating objects (i.e., getting a toy out of a tube; Cochet, 2011;Cochet et al, 2011;Fagard & Lockman, 2005). It could be argued that pointing to an object or extracting a toy from a tube is ''simpler'' than constructing models with LEGO 1 pieces.…”
Section: Discussionmentioning
confidence: 95%
“…There is also evidence that the reach-to-eat movement is distinguishable with respect to hand preference from other tasks that have been presented to infants. Right hand preference in performing tasks such as unscrewing a bottle, removing objects from a bottle (Fagard & Marks, 2000;Vauclair & Imbault, 2009), and removing rings from a column do not develop until 21 months of age (Cochet, 2011;Vauclair & Imbault, 2009), and much later for a wide range of other manual tasks (Cornwall, Harris, & Fitzgerald, 1991;Hopkins & Ronnqvist, 1998;Lewkowicz & Turkewitz, 1982;Peters, 1983).…”
Section: Developmental Psychobiologymentioning
confidence: 99%
“…Measures of handedness for manipulative actions would have provided an interesting comparison with the patterns of hand preference that were recorded for pointing. However, we decided to focus solely on hand preference for communicative gestures in the present study, as it has already been reported that hand preferences for pointing and for manipulative activities are not correlated (Bates et al, ; Cochet, ; Cochet & Vauclair, ). Moreover, the study by Knecht et al () revealed that 70% of left‐handers had left‐hemispheric control for speech, indicating that the relationship between handedness for manipulation and speech is, at best, very indirect.…”
Section: Discussionmentioning
confidence: 99%
“…With these methodological elements in mind, longitudinal observations over several months in infants and children have allowed researchers to identify different pathways in the development of handedness, depending on the activities considered and on individuals' patterns of HS (Cochet, 2012;Nelson et al, 2013). A first distinction has been highlighted between unimanual preference for grasping objects, which can be assessed from approximately 6 months of age, and bimanual preference for manipulating objects, with differentiated roles of the two hands: the hand regarded as non-dominant stabilizes the object for the manipulatory actions of the dominant hand (e.g., grasping a receptacle while picking up an object inserted in it).…”
Section: Grasping and Manipulating Objectsmentioning
confidence: 99%